Synthesis of the central tricyclic core of the isatisine A: harmonious orchestration of [metal]-catalyzed reactions in a sequence - Patel, Pitambar; Reddy, B. Narendraprasad; Ramana, C. V. (Tetrahedron, 2014)
Two sequential metal-catalyzed transformations, involving [In]-catalyzed Friedel Crafts type addition of spiroaminol carbon to indole C3 followed by [Rh]-catalyzed dehydrogenative cyclization of the resulting gamma-amino alcohol culminated in the construction of the central tricyclic core isatisine A. The overall strategy employed three easily available starting compounds and delivered the complex tricyclic core in four steps with all four steps being catalytic in nature. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Dehydrogenative cyclization; Friedel-Crafts reaction; Indium chloride; Isatisine A; Rhodium; Spiro-3-indolinone